Enhanced hemocompatibility and rapid magnetic anastomosis of electrospun small-diameter artificial vascular grafts - Liu, Peng; Liu, Xin; Yang, Lifei; Qian, Yerong; Lu, Qiang; Shi, Aihua; Wei, Shasha; Zhang, Xufeng; Lv, Yi; Xiang, Junxi (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Small-diameter (<6 mm) artificial vascular grafts (AVGs) are urgently required in vessel reconstructive surgery but constrained by suboptimal hemocompatibility and the complexity of anastomotic procedures. This study introduces coaxial electrospinning and magnetic anastomosis techniques to improve graft performance. Methods: Bilayer poly(lactide-co-caprolactone) (PLCL) grafts were fabricated by coaxial electrospinning to encapsulate heparin in the inner layer for anticoagulation. Magnetic rings were embedded at both ends of the nanofiber conduit to construct a magnetic anastomosis small-diameter AVG. Material properties were characterized by micromorphology, fourier transform infrared (FTIR) spectra, mechanical tests, in vitro heparin release and hemocompatibility. In vivo performance was evaluated in a rabbit model of inferior vena cava replacement. Results: Coaxial electrospinning produced PLCL/heparin grafts with sustained heparin release, lower platelet adhesion, prolonged clotting times, higher Young's modulus and tensile strength versus PLCL grafts. Magnetic anastomosis was significantly faster than suturing (3.65±0.83 vs 20.32±3.45 min, P<0.001) and with higher success rate (100% vs. 80%). Furthermore, magnetic AVG had higher short-term patency (2 days: 100% vs 60%; 7 days: 40% vs 0%) but similar long-term occlusion as sutured grafts. Conclusions: Coaxial electrospinning improved hemocompatibility and magnetic anastomosis enhanced implantability of small-diameter AVG. Short-term patency was excellent, but further optimization of anticoagulation is needed for long-term patency. This combinatorial approach holds promise for vascular graft engineering.